Docking, molecular dynamics and free energy studies on aspartoacylase mutations involved in Canavan disease - Kocak, Abdulkadir; Yildiz, Muslum (Elsevier Science Inc, 2017)
The disruption of aspartoacylase enzyme's catalytic activity causes fatal neurodegenerative Canavan disease. By molecular dynamics and docking methods, here we studied two deleterious mutations that have been identified in the Canavan patients' genotype E285A, F295S, and revealed the possible cause for the enzyme inhibition due to the drastic changes in active site dynamics, loss of interactions among Arg 71, Arg 168 and the substrate and pKa value of critical G1u178 residue. In addition to changes in the enzyme dynamics, free energy calculations show that the binding energy of substrate decreases dramatically up on mutations. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Neurodegenerative; Canavan; Docking; Molecular dynamics; ASPA; Mutation